The Existence of Public Relations in Higher Education Institutions in the Era of Globalization - Prastama, Reva Mahendra (Universitas Syiah Kuala, 2023)
Public Relations is a very questionable existence in the era of globalization with the emergence of many new technologies. in tertiary institutions as well, the existence of Public Relations regarding technical and managerial matters needs to be questioned. Competition between universities in this era of globalization, coupled with the increasingly critical nature of various groups in society, means that higher education institutions need to provide the best service to stakeholders, namely the community. In providing services to the community, the role of Public Relations is closely related to the relationship between the internal public and the external public in receiving and providing information regarding progress in an educational institution to build a positive image. The role of Public Relations in Higher Education Institutions is a strategic position to build public opinion or collaborate with the public. In this research, researchers used qualitative methodology with a case study method. The existence of Public Relations in higher education in this era of globalization continues to exist. From a managerial and technical perspective, Public Relations in higher education still plays a very important role in image building. It can also be said that within the framework of achieving higher education goals, the PR program in the technical context of strategic management should have a positive impact on stakeholders and the public.